NO2 and PM2.5 air pollution co-exposure and temperature effect modification on pre-mature mortality in advanced age: a longitudinal cohort study in China - John S. Ji; Linxin Liu; Junfeng (Jim); Haidong Kan; Bin Zhao; Katrin G. Burkart; Yi Zeng (BMC, 2022)
Abstract Background There is a discourse on whether air pollution mixture or air pollutant components are causally linked to increased mortality. In particular, there is uncertainty on whether the association of NO2 with mortality is independent of fine particulate matter (PM2.5). Furthermore, effect modification by temperature on air pollution-related mortality also needs more evidence. Methods We used the Chinese Longitudinal Healthy Longevity Study (CLHLS), a prospective cohort with geographical and socio-economic diversity in China. The participants were enrolled in 2008 or 2009 and followed up in 2011-2012, 2014, and 2017-2018. We used remote sensing and ground monitors to measure nitrogen dioxide (NO2), fine particulate matter (PM2.5) , and temperature. We used the Cox-proportional hazards model to examine the association between component and composite air pollution and all-cause mortality, adjusted for demographic characteristics, lifestyle, geographical attributes, and temperature. We used the restricted cubic spline to visualize the concentration-response curve. Results Our study included 11 835 individuals with an average age of ﻿86.9 (SD: 11.4) at baseline. Over 55 606 person-years of follow-up, we observed 8 216 mortality events. The average NO2 exposure was 19.1 μg/m3 (SD: 14.1); the average PM2.5 exposure was 52.8 μg/m3 (SD: 15.9). In the single pollutant models, the mortality HRs (95% CI) for 10 μg/m3 increase in annual average NO2 or PM2.5 was 1.114 (1.085, 1.143) and 1.244 (1.221, 1.268), respectively. In the multi-pollutant model co-adjusting for NO2 and PM2.5, the HR for NO2 turned insignificant: 0.978 (0.950, 1.008), but HR for PM2.5 was not altered: 1.252 (1.227, 1.279). PM2.5 and higher mortality association was robust, regardless of NO2. When acccounting for particulate matter, NO2 exposure appeared to be harmful in places of colder climates and higher seasonal temperature variation. Conclusions We see a robust relationship of PM2.5 exposure and premature mortality in advance aged individuals, however, NO2 exposure and mortality was only harmful in places of colder climate such as northeast China, indicating evidence of effect modification by temperature. Analysis of NO2 without accounting for its collinearity with PM2.5, may lead to overestimation.